A stretchable pressure sensor with interlinked interfaces prepared by a template-free process. (November 2022) - Liu, Meng-Yang; Zhao, Xue-Feng; Hang, Cheng-Zhou; Zhu, Li-Yuan; Wu, Xue-Yan; Wen, Xiao-Hong; Wang, Jia-Cheng; Lu, Hong-Liang
Highlights: An intrinsically stretchable pressure sensor array is developed by integrating stretchable electrode and sensing component. An AgNW/CNT electrode exhibits an enhanced stretching performance. The sensor exhibits outstanding stretchability, fidelity to dynamic pressure and durability even under 100 kPa. Abstract: A stretchable pressure sensor with interlinked interfaces was fabricated by a template-free process. The sensor was composed of stretchable silver nanowire (AgNW)/carbon nanotube (CNT) electrodes and piezoresistive polydimethylsiloxane (PDMS)/CNT foam. The electrode was fabricated by embedding conductive nanoparticles in PDMS, showing a low sheet resistance of 0.25 Ω sq −1, strain insensitivity, excellent stability, and durability over 2000 stretching/releasing cycles. The PDMS/CNT foam was fabricated through a solution-based process without a template exhibiting considerable piezoresistivity. By drop-casting and curing PDMS/CNT emulsion on the electrode, the electrode and foam can be bonded to form a stretchable pressure sensor seamlessly and directly. The sensor exhibited outstanding stretchability to 50%, high fidelity to dynamic pressure and great durability over 3000 loading/unloading cycles. In addition, a sensor array for pressure distribution detection was developed and confirmed to be able to withstand large deformations, such as stretching and poking.